Hubungan antara Komunikasi Dokter-Pasien dengan Kepuasan Pasien Rawat Inap di RSUD Sukoharjo - Wulandari, Fitria; , Drs. Mohammad Amir, M.Si (2016)
The inpatient patient's unsatisfaction can happen if the obtained service is not appropriate to the patient's hope. Communication from the doctor to the patient is one of factors that can influence the inpatient patient's satisfaction. The purposes of this research are: 1) To know the correlation between doctor-patient communication and inpatient patient's satisfaction in RSUD (Public Regional Hospital) of Sukoharjo 2) To know the effective contribution of doctor-patient communication on the inpatient patient's satisfaction in RSUD Sukoharjo 3) To know the level of inpatient patient's satisfaction in RSUD Sukoharjo 4) To know the level of the doctor-patient communication in RSUD Sukoharjo. Subjects in this research are the inpatient patients in RSUD Sukoharjo as much as 100 people. The technique of sampling which was used was purposive sampling. The method of data collection used the scale of doctor-patient communication and the scale of inpatient patient's satisfaction. The technique of data analysis used correlation of product moment. Based on the results of Product moment, it was obtained the score of coefficient of rxy correlation as much as 0.795; (p) = 0.000 (p<0.01) which meant that there was a positive significant correlation between the doctor-patient communication and the inpatient patient's satisfaction. The effective contribution of the both variables was showerd by the coefficient of determinant (r²) = 0.63 which showed that the doctor-patient communication influenced the inpatient patient's satisfaction as much as 63%, meanwhile, 37% of the rest was infleunced by other variables. Subjects in this research had a level of doctor-patient communication in the high category with an empirical mean as much as = 102.26 and the hypothetical mean as much as = 75. The subjects also had a high inpatient patient's sastisfaction with an empirical mean as much as = 148.99 and the hypothetical mean as much as = 115.